2020
DOI: 10.1101/2020.03.10.20033944
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virus strain of a mild COVID-19 patient in Hangzhou represents a new trend in SARS-CoV-2 evolution related to Furin cleavage site

Abstract: The outbreak of COVID-19 become enormous threat to human beings, showing unclear virus mutation during dissemination. We found, in our 788 confirmed COVID-19 patients, the decreased rate of severe/critical type, increased liver/kidney damage and prolonged period of nuclear acid positivity, when compared with Wuhan.To investigate underlining mechanisms, we isolated one strain of SARS-CoV-2 (ZJ01) in mild COVID-19 patient and found the existence of 35 specific gene mutation by gene alignment. Further phylogeneti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
(67 reference statements)
0
14
0
Order By: Relevance
“…In another study, Xi et al (2020) isolated one strain of SARS-CoV-2 (ZJ01) in mild COVID-19 patient and reported the presence of more than 30 specific gene mutation. The theoretical analysis of FCS and the case alignment of CoV family determined that FCS may be a crucial site of CoV evolution.…”
Section: Furin Cleavage Sitementioning
confidence: 99%
See 2 more Smart Citations
“…In another study, Xi et al (2020) isolated one strain of SARS-CoV-2 (ZJ01) in mild COVID-19 patient and reported the presence of more than 30 specific gene mutation. The theoretical analysis of FCS and the case alignment of CoV family determined that FCS may be a crucial site of CoV evolution.…”
Section: Furin Cleavage Sitementioning
confidence: 99%
“…GZ02 presented a number of negative charge distribution in F3 site while limited negative charge distribution was observed in SARS-CoV-2-associated virus (Figure 4a). Hence, they deduced that, the mutation close to FCS site lead to a significant change in the protein conformation and surface charges, which further affected its interaction with the ligands (Xi et al, 2020). Hoffmann et al (2020) depicted that SARS-CoV-2 cell entry relied on ACE-2 and TMPRSS2 and is limited by a protease inhibitor.…”
Section: Furin Cleavage Sitementioning
confidence: 99%
See 1 more Smart Citation
“…The genetic susceptibility to has also been explored by scrutinizing Angiotensin converting enzyme 2 (ACE2) genetic variations in different populations. ACE2 is the functional receptor mediating entry of SARS-CoV-2 into the host cells 5 , which is facilitated by FURIN cleavage [6][7][8] . Transmembrane serine protease 2 (TMPRSS2) is another candidate gene that has been linked to COVID-19 disease [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…The hallmark of the novel SARS-CoV-2, as compared to other SARS viruses, is the presence of a polybasic FURIN cleavage site. FURIN has been reported to facilitate the transport of SARS-CoV-2 into or from the host cell [6][7][8] . Notably, a recent study has highlighted the presence of a unique functional polybasic FURIN cleavage consensus site between the two spike subunits S1 and S2 by the insertion of 12 nucleotides encoding PRRA in the S protein of SARS-CoV-2 virus 12 .…”
Section: Introductionmentioning
confidence: 99%